Sexual history and examination in men and women. (April 2022) - Henderson, Merle; Herbert, Sophie
Abstract: Taking a sexual history and undertaking a genital examination are not skills regularly used in general medicine. While the structure and process of history-taking and clinical examination follow that seen in other medical specialties, aspects unique to taking a history that covers intimate subject matter require additional empathy, sensitivity and non-verbal skills, to enable clinicians to obtain the information needed to undertake an appropriately thorough assessment. Telemedicine has also become a routinely used way to assess some patients and requires some adaptation to these skills. This article aims to simplify sexual history-taking and examination, providing tips on how to do it well, whatever the setting.